2017
DOI: 10.1038/s41598-017-00617-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes related to salt stress tolerance using intron-length polymorphic markers, association mapping and virus-induced gene silencing in cotton

Abstract: Intron length polymorphisms (ILPs), a type of gene-based functional marker, could themselves be related to the particular traits. Here, we developed a genome-wide cotton ILPs based on orthologs annotation from two sequenced diploid species, A-genome Gossypium arboreum and D-genome G. raimondii. We identified 10,180 putative ILP markers from 5,021 orthologous genes. Among these, 535 ILP markers from 9 gene families related to stress were selected for experimental verification. Polymorphic rates were 72.71% betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 78 publications
2
17
1
Order By: Relevance
“…Significantly higher variation was observed also for SNPs in noncoding regions compared to coding ones [42]. In general, introns are more variable than exons, as they are under less selection pressure during the evolutionary process [43].…”
Section: Discussionmentioning
confidence: 94%
“…Significantly higher variation was observed also for SNPs in noncoding regions compared to coding ones [42]. In general, introns are more variable than exons, as they are under less selection pressure during the evolutionary process [43].…”
Section: Discussionmentioning
confidence: 94%
“… Jia et al (2014a) only detected three SSR markers associated with salt tolerance in MLM using 106 SSRs in 323 G. hirsutum germplasms. Cai et al (2017) found 9 intron length polymorphisms (ILPs) markers for 10 salt stress traits with 535 ILP markers in 264 G. hirsutum accessions. In this study, 713 upland cotton accessions were used to conduct a GWAS of two salt-tolerance related traits with 10,511 SNPs, and we identified 10 and 15 loci for RSR and STL, respectively, of which two common SNP loci (i46598Gh and i47388Gh) on D09 were significantly associated with the two traits.…”
Section: Discussionmentioning
confidence: 99%
“…A salt-tolerant cultivar (Suwu77-702) and a salt-sensitive cultivar (Shann424) were selected to grow for 7 days in a germination box, and then moved into 1/2 Hogland nutrient solution until the three-true-leaf period (about another 14 days). Under 200 mmol/L NaCl stress, leaves were sampled at 0, 3, 6, 8, 12, 24, and 48 h for measuring the content of the protein, POD, MDA, and H 2 O 2 ( Liu and Li, 2007 ; Cai et al, 2017 ). Three biological replicates were performed.…”
Section: Methodsmentioning
confidence: 99%
“…In the past 12 years the website has been visited more than 12 636 545 times by users in more than 186 countries and regions (as of the end of 2017). WEGO was cited over 1536 times by publications covering research topics focusing on various types of species from Bryum argenteum (Bryophytes) ( 23 ) to Polynoidae (scale worms) ( 24 ) and from Gossypium (cotton) ( 25 ) to Bombus terrestris (bumblebee) ( 26 ). We have also benefitted from a great deal of positive feedback and some very constructive suggestions from users worldwide.…”
Section: Introductionmentioning
confidence: 99%